2017
DOI: 10.1007/s11661-017-4162-2
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Analyses of ATI 718Plus® Produced by Wire-ARC Additive Manufacturing Process

Abstract: A detailed microstructural study of ATI 718Plus superalloy produced by the wire-arc additive manufacturing (WAAM) process was performed through the use of scanning electron microscopy (SEM), transmission electron microscopy (TEM), electron probe micro-analysis (EPMA), and electron backscatter diffraction (EBSD). Extensive formation of eutectic solidification microconstituents including Laves and MC-type carbide phases, induced by micro-segregation, are observed in the build of the alloy in the as-deposited con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…The local composition of the microstructure in Alloy 718 differs from its nominal composition value because of the segregation of the elements during solidification. A segregated microstructure behaves in a different manner compared with a microstructure in the nominal composition of the same alloy, [25] which is illustrated based on the CCT diagrams obtained (as explained in Section III-C) for Alloy 718 in the following.…”
Section: Change In Precipitation Kinetics Of Phases In the Microstmentioning
confidence: 99%
“…The local composition of the microstructure in Alloy 718 differs from its nominal composition value because of the segregation of the elements during solidification. A segregated microstructure behaves in a different manner compared with a microstructure in the nominal composition of the same alloy, [25] which is illustrated based on the CCT diagrams obtained (as explained in Section III-C) for Alloy 718 in the following.…”
Section: Change In Precipitation Kinetics Of Phases In the Microstmentioning
confidence: 99%
“…Jinguo et al [7] investigated the cooling rate and 2 of 12 microstructure changes based on the height of the deposit in the cold metal transfer-WAAM process using 2Cr13 stainless steel; the authors claimed that the martensite content in the microstructure formed in each layer varied with the differences in the cooling rates of each layer. Asala et al [8] measured the temperature history during WAAM using Inconel 718, and studied the microstructure variation with respect to the height of the deposit; they observed that the lower and middle parts of the deposit remained for a longer period within the aging-temperature range of Inconel 718 during deposition compared to the upper part, resulting in increased precipitation hardening in the microstructure, thereby demonstrating enhanced mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Wire + Arc additive Manufacturing (WAAM), which employs an electric arc as the heat source, and high-quality metal wire as the feedstock [19], can directly fabricate fully-dense large 3-D near-net-shape components, at much higher rates, than most other metal AM processes [18,19], the highest rate so far being of 9.5 kg/h [20]. The WAAM process has successfully produced large-scale parts in stainless steel [21], Inconel ® [22], titanium [23] and aluminium [24]. Furthermore, a previous research showed that unalloyed tungsten can be deposited via WAAM with a noteworthy absence of micro-cracks among the layers [25].…”
Section: Introductionmentioning
confidence: 99%